Newborn infant of a mother with leptospirosis: A case report - Cisneros-Infantas, Luz (2019)
Human leptospirosis is a disease caused by bacteria of the genus Leptospira. Leptospiras infect the body through the skin and damaged mucous membranes. At the site of admission, they produce little local inflammatory reaction. Clinical symptoms range from flu-like symptoms to jaundice or even kidney and liver failure, and are associated with high mortality rates. It is known that there is a transplacental infection that can cause miscarriage, fetal death or congenital leptospirosis. Miscarriage is more common if the infection occurs in the first months of pregnancy. The objective of this case report is to disclose the presentation, manifestations and therapeutic approach in intensive care of a newborn infant with maternal history of leptospirosis in the first trimester of pregnancy, as well as the review of the literature using a systematic search.